Extracellular polymeric substances production in sludge by bacteria isolated from Hanoi brewery - Van, Nguyen Hai; Ngoc Anh, Dao Thi; Huyen Trang, Ngo Thi; Trung, Nguyen Duy; Hoang, Nguyen Viet; Duong, Nguyen Mai; Cam Ha, Dang Thi (Academia Journal of Biology, 2015)
In general, chemical flocculates commonly used in wastewater treatment are known to be expensive and ultimate disposal costs. In order to solve these problems, production of biopolymer from bacteria through re-use of municipal wastewater sludge has been studied because of its sustainability, safety and economics. In this study, 10 EPS producing bacterial strains were isolated from wastewater treatment plant of Hanoi brewery. These bacterial strains were cultured in sterilized sludge for EPS production. Flocculation activity and EPS compositions included dry weight, concentration of carbohydrate and protein were analyzed. All examined bacterial strains isolated showed clearly ability of flocs formation, the kaolin clay flocculation activity with presence of 150 mg Ca2+/l achieved from the study ranged from 36 to 80% when 0.5-6 ml volume of EPS was added. EPS concentration of 10 bacteria strains varied from 2737 to 5018 mg/l. One out of ten strains, BES 19 bacteria provided the highest flocculation activity of 80% with LB-EPS and TB-EPS concentrations at 4,330 mg/l and 689 mg/l, respectively. BES19 strain was classified based on sequence of full 16S rRNA coding gene. This bacterium belonged to Bacillus genus and named Bacillus sp. BES19. These results provide basics for production of biopolymer which are sustainable and renewable.